Mechanisms of formation of maladaptation states among internship doctors and approaches to their correction - V. V. Vyun (Kazimierz Wielki University, 2016)
A doctor's adaptation to medical activity has a great influence on the effectiveness of his professional activity. The objective: to explore individual psychological predictors of the formation of maladaptation states of internship doctors for the development of a system for their diagnosis, correction and psychoprophylaxis. A comprehensive clinical-psychological, psychodiagnostic and clinical-anamnestic examination of 213 internship doctors of the first year of training atKharkovNationalMedicalUniversity, 116 women and 97 men, aged 22-25 years old had been conducted. It had been established that internship doctors are characterized by feelings of internal tension and dissatisfaction, decreased mood, irritability, anxiety, long-term uncertain negative emotions, unmotivated fears, self-doubt, doubts about making decisions, decline in intellectual activityin conjunction with increased exhaustion and withdrawal mercurial attention. We have developed a system of medical and psychological support during the professional training period depending on the type of disadaptation. The psychotherapeutic complex in the internship doctors included the use of rational psychotherapy, autogenous training (psychotonic version of Shogham-Mirovsky), art therapy, progressive muscle relaxation by Jacobson, cognitive-behavioral therapy of Beck, autogenous training in the modification of Lebedinsky - Bortnik, etc. were used. The results of a three-year catamnestic study proved the effectiveness of the proposed system of psychotherapeutic correction of disorders of adaptation, positive dynamics of the mental state was noted, the maladaptive states were reduced; 92.6% of the examined recurrences of the violations of adaptation did not occur.